The ginsenoside metabolite compound K inhibits hormone-independent breast cancer through downregulation of cyclin D1. (July 2018) - Lee, Seung Joon; Lee, Ji Su; Lee, Eunjung; Lim, Tae-Gyu; Byun, Sanguine
Graphical abstract: Highlights: CK is the most potent ginsenoside against breast cancer. CK inhibits breast cancer tumor growth in vivo. CK induces G1 cell cycle arrest in hormone-independent breast cancer cells. CK suppresses cyclin D1 expression through proteasomal degradation. Abstract: Various types of ginsenosides are present in ginseng and have been recognized for their health-promoting effects. Compound K (CK) is a metabolite of ginsenoside Rb1 and reportedly exerts chemotherapeutic effects against several types of cancers. However, the anti-cancer effect and the molecular mechanism of CK against hormone-independent breast cancer is unknown. Through a direct comparison, it was discovered that CK elicits the strongest anti-cancer effect against breast cancer cells when compared to other ginsenosides. CK treatment suppresses the growth of hormone-independent human breast cancer cells and induces G1 phase cell cycle arrest. CK also markedly suppresses tumor growth in a mouse xenograft model, concomitant with the suppression of cyclin D1 via protein degradation. These findings suggest that CK can be used to target hormone-independent breast cancers by inducing degradation of cyclin D1.